Measurement of body composition by deuterium oxide dilution technique and development of a predictive equation for body fat mass among severe neurologically impaired children - Sakamornchai, Wirada; Dumrongwongsiri, Oraporn; Phosuwattanakul, Jeeraparn; Siwarom, Sirinapa (Frontiers in Nutrition, 2023)
Introduction: Neurologically impaired (NI) children are at risk of malnutrition, which consequently impacts their health and quality of life. Accurate nutrition assessment is an important step to guide appropriate nutrition support. Conventional anthropometric measurements among NI children have some limitations. Determining body composition requires more complex equipment which are not routinely performed. This study was conducted to evaluate the association between anthropometric parameters and body composition assessed by deuterium dilution technique (DDT) in NI children. Methods: A cross-sectional study enrolled severe NI children aged 1-20 years who received home enteral nutrition for at least 3 months. Weight, length, and 4-site skinfold thickness were measured. Body composition was determined by DDT following the International Atomic Energy Agency (IAEA) protocol. Results: Thirty-seven of NI children (56.76% male, median age 7.2 years) were enrolled. The prevalence of underweight, stunting and overweight were 22, 38, and 35%, respectively. Body composition analysis showed mean (SD) of total body water (TBW) and fat mass (FM) were 10.52 (4.51) kg and 9.51 (6.04) kg, respectively. Multivariate GLM analysis showed that the factors associated with FM were age (β=0.07 [0.05,0.08]; p<0.001), body mass index (BMI) (β=0.82 [0.52, 1.12]; p<0.001), and biceps skinfold thickness (BSF) (β=0.49 [0.23,0.75]; p=0.001) and subscapular skinfold thickness (SSF) (β=-0.24 [-0.46,0.03]; p=0.030). A predictive equation for FM was constructed. Conclusion: High prevalence of malnutrition was found among severe NI children despite enteral nutrition support. Our findings showed that age, BMI BSF, and SSF were associated with FM. The predictive equation of FM was proposed and needed to be further validated and applied to use in clinical practice.